PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE ANIMATE MATA PELAJARAN ANIMASI 2 DIMENSI: STUDI KASUS SMK NEGERI 1 BUNGO - Dian Aji Saputra; Yogi Irdes Putra; Fauziah F (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
Based on the observation, the teacher has not used interesting learning media, the learning media used is only in the form of whiteboard media and powerpoint media, where the media used has not been able to help deliver the material accurately and clearly so that students do not understand the material being taught. Limited material sources are only in the form of textbooks that are no longer suitable for use and are only owned by the teacher, so students have difficulty reviewing the material independently. Based on these problems, this research aims to develop interactive learning media based on Adobe Animate that is valid, practical, and effective in 2-dimensional animation subjects. This type of development research is Research and Development (R&D) with the 4D (four-D) development model which consists of four stages, namely, (1) Define, (2) Design, (3) Develop, and (4) Disseminate. The results of this development research are obtained based on the results of the development test. (1) Validity test, the results obtained were 0.79 (media aspects) and 0.82 (material aspects) with valid categories. (2) Practicality test, with a teacher response of 82.35% and a student response of 81.32% with a practical category. (3) Effectiveness test, obtained from student learning outcomes that reached 86.7% KKM classically and the results of paired t test data analysis showed an increase between Pretest and Posttest of -9.9604. Based on the test results obtained, it is concluded that the interactive media is effective.